2012
DOI: 10.1111/j.1364-3703.2011.00778.x
|View full text |Cite
|
Sign up to set email alerts
|

BcAtf1, a global regulator, controls various differentiation processes and phytotoxin production inBotrytis cinerea

Abstract: Atf1-homologous basic region leucine zipper (bZIP) transcription factors are known to act downstream of the stress-activated mitogen-activated protein kinase (SAPK) cascade in mammals, as well as in several fungi; they regulate the transcription of genes involved in the general stress response. Functional analyses of BcAtf1 in Botrytis cinerea show that it is also connected to the SAPK BcSak1, as it shares several stress response target genes. However, Δbcatf1 mutants are not hypersensitive to osmotic or oxida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
77
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(82 citation statements)
references
References 77 publications
(102 reference statements)
3
77
0
Order By: Relevance
“…According to our results, genes belonging to bZIP-type family stand as important elements in the mechanism of action of piperine. As previously mentioned, these bZIP elements play a critical role in modulating secondary metabolite production in response to different types of stresses, thus standing as key elements in fungal adaptation to different environmental stimuli Temme et al, 2012;Van Nguyen et al, 2013;Yin et al, 2012Yin et al, , 2013. For instance, Ap-1, belonging to a redox-state sensor protein family, maintains highly conserved functions in mammalian, yeast and fungi (Toone et al, 2001).…”
Section: Piperine Inhibits Afb1 Production and Modulates Bzip Transcrmentioning
confidence: 99%
“…According to our results, genes belonging to bZIP-type family stand as important elements in the mechanism of action of piperine. As previously mentioned, these bZIP elements play a critical role in modulating secondary metabolite production in response to different types of stresses, thus standing as key elements in fungal adaptation to different environmental stimuli Temme et al, 2012;Van Nguyen et al, 2013;Yin et al, 2012Yin et al, , 2013. For instance, Ap-1, belonging to a redox-state sensor protein family, maintains highly conserved functions in mammalian, yeast and fungi (Toone et al, 2001).…”
Section: Piperine Inhibits Afb1 Production and Modulates Bzip Transcrmentioning
confidence: 99%
“…As the strain is highly virulent on several host plants and yields consistently high transformation rates it has become one of the standard recipient strains in most laboratories. The genomes of B05.10 and T4 (a less aggressive isolate) were sequenced in recent years (Amselem et al, 2011) enabling detailed molecular analyses such as transcriptomic and proteomic approaches (Temme et al, 2012;Fernández-Acero et al, 2006Shah et al, 2009a,b;Espino et al, 2010). Available genome sequences and a more efficient system for construction of replacement fragments by yeast recombinational cloning such as those used by Colot et al (2006) has resulted in the rapid expansion of the number of functionally analyzed genes in B. cinerea.…”
Section: Introductionmentioning
confidence: 99%
“…It is likely that the BcSak1 pathway regulates the expression of the Bcbot genes in response to oxidative stress even though there is no evidence that the known downstream TF i.e. BcAtf1 directly acts on the BOT gene cluster (Temme et al, 2012).…”
Section: Botrydial Biosynthesis Depends On the Putative Pathway-specimentioning
confidence: 99%
“…The second is the stress-induced MAP kinase cascade with the downstream bZIP TF BcAtf1 (Temme et al, 2012) and the BcReg1 transcriptional regulator (Michielse et al, 2011). In addition, it was demonstrated that B. cinerea secondary metabolism is greatly influenced by light-dependent development .…”
Section: Introductionmentioning
confidence: 99%